A new modified compact finite difference scheme for solving the generalized Burgers-Huxley equation in teaching and learning processes - Rabi’atul ‘Aisyah Rusli,; Mohd Agos Salim Nasir,; Nurzalina Harun,; Sidik Rathi,; Zubaidah Sadikin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this study, a new modified scheme based on compact finite difference technique has been proposed for approximate the solution of the generalized Burgers-Huxley equation. The basic idea of compact finite difference scheme is to find the compact approximations to the derivatives terms by manipulating the governing equation. This basic concept is suitable to be introduced in teaching and learning processes for the Generalized Burgers – Huxley equation. The numerical experiments on the proposed scheme have been conducted and all the computations were carried out by MATLAB R2010a software. The results are compared with analytical solutions and the solution obtained by other researchers. Encouraging results have been obtained. Comparative study shows that the compact finite difference scheme produces better accuracy than the scheme cited in the literature. The compact finite difference scheme exhibits reliable method for solving the generalized Burgers-Huxley equation.